ANALISIS COMMON SIZE DAN RASIO PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN TERHADAP PT ASTRA INTERNATIONAL TBK PERIODE 2013–2023 - Nisa Nuraisyah, Ajeng; Satria, Rita (Journal of Research and Publication Innovation, 2024)
This study aims to determine how the financial performance of PT Astra International Tbk, based on common size analysis and profitability ratios (Gross Profit Margin, Return on Assets, and Return On Equity). The research method used is quantitative descriptive method and secondary data collection. The results of the analysis in general based on common size analysis, the performance of PT Astra International from 2013 to 2023 measured using common size analysis is fairly good, although current assets tend to decrease but non-current assets show an increase and total equity has a higher average value than average debt. The profitability position can be seen that the average gross profit margin is 20.98%, the average return on assets is 8.06%, and the average return on equity is 15.02% which means it is below the industry average. The financial performance of PT Astra International Tbk in 2013-2023 experienced an unhealthy situation. This shows that the company has not been able to utilize assets and capital in generating net income.